Targeted Therapy and Immunotherapy Response Assessment with F-18 Fluorothymidine Positron-Emission Tomography/Magnetic Resonance Imaging in Melanoma Brain Metastasis: A Pilot Study - Nguyen, Nghi C.; Yee, Melissa K.; Tuchayi, Abuzar M.; Kirkwood, John M.; Tawbi, Hussein; Mountz, James M. (Frontiers in Oncology, 2018)
Introduction: This pilot study aimed at exploring the utility of the proliferation tracer F-18 FLT (FLT) and PET/MRI (FLT-PET/MRI) for early treatment monitoring in patients with melanoma brain metastasis (MBM) who undergo targeted therapy or immunotherapy. Material and Methods: Patients with newly diagnosed MBM underwent baseline and follow-up FLT-PET/MRI scans at 3-4 weeks of targeted therapy or immunotherapy. Up to 6 measurable brain lesions ≥ 1.0 cm per subject, as identified on T1-weighted post-Gd images, were included for quantitative analyses. The maximum SUV of each lesion was divided by the mean SUV of the pons to obtain the SUV ratio (SUVR). Results: Five enrolled subjects underwent the baseline FLT-PET/MRI study in which the MBM showed a median size of 1.7 cm (range 1.0-2.9) and increased metabolic activity with SUVR of 9.9 (range 3.2-18.4). However, only two subjects (cases #1 and #2) returned for a follow-up scan. At baseline, a total of 22 lesions were analyzed in all five subjects, which showed a median size of 1.7 cm (range 1.0-2.9) and median SUVR of 9.9 (range 3.2-18.4). At follow-up, case #1 was a 55-year-old man who received targeted BRAF inhibitor and MEK inhibitor therapy with dabrafenib and trametinib. Fused PET/MRI data of 6 measured lesions demonstrated a significant reduction in MBM proliferative activity (median -68%; range -38% to -77%) and size (median -23%; range -4% to -55%) at three weeks of therapy. Nevertheless, the subject eventually progressed and died 13 months after therapy initiation. Case #2 was a 36-year-old man who received immunotherapy with nivolumab and ipilimumab. The five measured MBM lesions showed a mixed response at both proliferative and morphologic imaging at one-month follow-up. Some lesions demonstrated interval decrease while others interval increase in proliferative activity with a median -44% (range -77% to +68%). On MRI, the size change was +7% (range -64% to +50%). The therapy was switched to dabrafenib and trametinib, which led to a partial response. The patient is still alive 16 months following therapy initiation. Conclusion: The five cases presented show the potential benefit of hybrid FLT-PET/MRI for the diagnosis of MBM and treatment monitoring of